2008
DOI: 10.1007/s00586-007-0567-8
|View full text |Cite
|
Sign up to set email alerts
|

A screening questionnaire to predict no return to work within 3 months for low back pain claimants

Abstract: The objective of the present study was to develop a short prediction questionnaire for estimating the risk of no return to work (RTW) within 3 months of sick leave to facilitate triage and management of a patient population of subacute low-back pain (LBP) sufferers. We conducted a prospective study with a 3-month follow-up on 186 patients with LBP introducing a claim for sickness benefits to the largest sickness fund in Belgium. Patients completed a screening questionnaire within 2 weeks after claim submission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 24 publications
3
17
0
Order By: Relevance
“…The finding that expectations regarding RTW at baseline predict NRTW at 2 years is consistent with previous research in general injury cohorts [18][19][20][21][22][23][24][25][26] . This study is the first to demonstrate that this factor predicts RTW in a RTC cohort.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The finding that expectations regarding RTW at baseline predict NRTW at 2 years is consistent with previous research in general injury cohorts [18][19][20][21][22][23][24][25][26] . This study is the first to demonstrate that this factor predicts RTW in a RTC cohort.…”
Section: Discussionsupporting
confidence: 89%
“…This suggests that developing a screening tool to detect individuals at risk of NRTW would be beneficial, since appropriate and effective interventions to increase the RTW rate could be offered. The two-item measure is short (5-10 minutes to complete) and simple to administer and answer, meaning that non-specialists can easily score the items and determine whether someone is at-risk of NRTW.The finding that expectations regarding RTW at baseline predict NRTW at 2 years is consistent with previous research in general injury cohorts [18][19][20][21][22][23][24][25][26] . This study is the first to demonstrate that this factor predicts RTW in a RTC cohort.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…In this domain of research, recovery expectancies have been broadly conceptualized as the injured individual's prediction of the likelihood of recovery [21][22][23]. Cole et al [19] reported that injured workers' expectations of slower recovery were consistently associated with longer duration of time loss claims.…”
Section: Introductionmentioning
confidence: 99%
“…A randomized controlled trial showed that LBP patients who were provided information and advice by the medical advisers of the Alliance of Christian Sickness Fund experienced a significantly higher return to work rate due to a low relapse rate [34]. A practical screening tool to identify patients at risk of long-term sick leave may further enhance cost-effectiveness [35]. In case of severe relapsing low back pain despite conservative treatment and when surgery is perceived as an invaluable option, intervention needs to be performed without undue delay [36][37][38].…”
Section: Resultsmentioning
confidence: 99%